Body Mass Index as a predictor of multimorbidity in the Brazilian population - Marina Christofoletti; Anne Ribeiro Streb; Giovani Firpo Del Duca (Universidade Federal de Santa Catarina, 2018)
Overweight is a health risk indicator, but little is known about its influence on the chronic non-communicable diseases (NCD) multimorbidity. The aim of this study was to identify the predictive values   and sociodemographic factors associated with Body Mass Index (BMI) as a determinant of the occurrence of NCD multimorbidity in Brazilian men and women. Data from the "Surveillance of risk and protection factors for chronic diseases by telephone survey" - 2013 national survey were used. The population was composed of ≥18 year-old individuals and those living in house with a fixed telephone line in the 27 Brazilian's capitals. The outcome variables were BMI and its respective predictive value for the occurrence of multimorbidity (≥2 NCDs). The exposure was age, marital status and educational level. Inferential statistics included the construction of Receiver Operating Characteristic curves (cutoff point defined by sensibility [Se] and specificity [Sp]) and the association by Poisson Regression, stratified by sex. The values with the best predictive capacity for multimorbidity were 26.7 kg/m² (Se = 60.9%, Sp = 60.2%) for men and 25.7 kg/m² (Se = 61.8%, Sp = 61.1%) for women. The predictive multimorbidity value followed the progress of age groups up to 55 to 64 years for both groups. Women with higher educational level showed an inverse association for the presence of the outcome. BMI can be considered a predictor of the occurrence of multimorbidity, and sociodemographic profile associated with this predictive value was advancement age and inversely associated with educational level in women.